A Village on the Outskirts of the Ottoman Empire: Archaeological Research at Tell Zeyd - Tonghini, Cristina; Boschini, Jacopo; Palalidis, Stefano; Bangsborg Thuesen, Mette (Annali di Ca’ Foscari: Serie Orientale, 2025)
This paper presents the most recent results from the research programme Zeyd Archaeological Project; launched in 2022, this project aims at exploring economy and society in the hinterland of the historical province of Mosul in the long Islamic period focusing on a highly representative site of the area, Tell Zeyd. Three seasons of archaeological research at the site have made it possible to put together a rich assemblage of data that illustrates settlement patterns and production at the village in the Ottoman period. This paper focuses on the evidence that emerged from the 2024 excavations, and, more specifically, on the occupation phases that can be ascribed to the Early Ottoman period (Period E), datable to around the sixteenth century.